Cyclic Oxidation Kinetics and Thermal Stress Evolution of TiAl Alloys at High Temperature - Shiwei Tian; Tengkun Zhang; Shangwu Zeng; Yefei Zhang; Dejun Song; Yulai Chen; Qiang Kang; Haitao Jiang (Metals, 2023)
The oxidation resistance of TiAl alloys is crucial for their commercial application. In this paper, a cyclic oxidation test with stable air circulation was designed to investigate the cyclic oxidation behavior of the TNM alloy and 4822 alloy at 800 °C and to analyze the phase, morphology, and thermal stress evolution of the oxide layer. The oxidation weight gain curves of both alloys are found to be in parabolic form, and the oxidation reaction orders of the TNM alloy and 4822 alloy are 2.374 and 1.838, respectively. The Nb and Mo elements enhance the antioxidant performance of the TNM alloy by inhibiting the dissolution and diffusion of oxygen, Ti, and Al atoms in the TiAl alloy. The thermal stress evolution of the two alloys during the heating and cooling phases of the cyclic oxidation process are calculated separately, and it is found that the thermal stresses in the TNM alloy are smaller than those in the 4822 alloy, while the maximum thermal stresses appear at the oxide/substrate interface rather than inside the oxide scale, which quantitatively explains the oxidation peeling resistance of the two alloys.